Convergence of the spectral decomposition of a function from the class $W_{p,m}^1 (G),\; p > 1$, in the vector eigenfunctions of a differential operator of the third order - Abbasova, Yu. G.; Kurbanov, V. M. (Ukrains’kyi Matematychnyi Zhurnal, 2017)
We consider, a third-order differential operator with matrix coefficients. The absolute and uniform convergence of theorthogonal expansion of a vector function from the class $W_{p,m}^1 (G),\; p > 1$, in the vector eigenfunctions of this operator isstudied and the rate of uniform convergence of this expansion on $G = [0, 1]$ is estimated.